Promoting Bike Helmet Safety for Urban Children Through a Culturally Tailored Educational Video Intervention. Issue 2 (March 2019) - Ryan, Leticia Manning; Solomon, Barry S.; Ziegfeld, Susan; Gielen, Andrea; Malloy, Lauren; Foster, Daniel; Smith, Katherine Clegg; McDonald, Eileen
Bicycle-related falls are a significant cause of mortality and morbidity. Use of bicycle helmets substantially reduces risk of severe traumatic brain injury but compliance with this safety practice is particularly low in urban children. We recruited eleven 8- to 15-year-old youth to participate in focus groups to inform the creation of a video promoting helmet use. Key emerging themes included that youth were responsible for keeping themselves safe and that most youth had cell phones with cases to protect them. A video was created that linked the concept of use of cases to protect phones to use of helmets to protect heads. Soliciting information from urban youth was helpful for developing this educational video.